Siti e monumenti di interesse storico nella Terra Vittoria, documenti della presenza umana in Antartide. - BARONI, CARLO (Società Geografica Italiana, 1994)
Historic Sites and Monuments of the Victoria Land, Heritage of human Presence in Antartica Several huts and monuments of historic interest are still preserved in Antarctica. They represent the heritage of the expeditions of the Heroic Age and are protected bv the Antarctic Treaty which recognizes 53 sites of historic interest. Victoria Land was discovered bv Sir James Clark Ross in 1841 and cherishes several historic huts, mainly related to British Antarctic Expeditions which took quarters on Ross Island, from where they started to conquer the polar plateau. Conservancy and restoration of the historic sites started in the '60s by the New Zealandes. The care of historic sites allows us to study them from different points of view. They contribute to study the history of exploration and scientific research as well as Antropic Geography. Archaeological excavations of the huts and of the neighbouring areas contribute to our understanding of the activities that took place there and can corroborate or correct the contemporaneous written reports. Furthermore, the ice-free areas ncar the historic sites (expecially if protected from later disturbance) supply precious environmental informations very useful to evaluate the impact of modern Antarctic bases. From a certain point of view there are other sites which can assume an important historic significance as, for instance, the sites of the oldest landings, the most significative places of explorations (Beardmore Glacier, Backstairs Passage, etc.) and the fossiliferous localities discovered in Antarctica as first steps of scientific discoveries.